The Effect of Chlorine on The Reduction of Coliform and Total Suspended Solids in Domestic Wastewater at Port X Batam City - Saputra, Roni; Gemala, Mega; Ginting, Risa Astriani; Ahmadi, Ahmadi (Miracle Journal of Public Health, 2025)
Daily activities at Port X produced domestic liquid wastewater with total coliform and TSS parametersexceeding the required quality standards. Total coliforms and TSS polluted waterbodies and causedgastrointestinal diseases in humans. The aim of this research was to see the effect of chlorine on reducing totalcoliforms and TSS in domestic wastewater from Port X Batam City in 2024. This research used trueexperimental method with a pretest - posttest control group design. Primary data was obtained by treatmentand examination in the laboratory. Data were analyzed using a paired t-test to see the effect on the controlgroup and treatment group (p value <0.05). The research results showed that there was an effect of theindependent variable towards the dependent variable. The most influential treatment was a chlorine dose of 2gr/l and aeration for 4 hours with a percentage reduction in the total number of coliforms and TSS levels of82.71% and 85.16% respectively. Based on the research results, it can be concluded that chlorine had an effecton reducing the total number of coliforms and TSS levels in Port X domestic waste samples.Keywords: Chlorine, wastewater, Stirring, aeration